The Use of Family Documents in Historical Writings: The Book "Documentary Studies in the Contemporary History of Iraq" as a Model - Dheerb, Dr.Muntaser Hasen; Jidou, Moayad Fadel (Thi Qar Arts Journal, 2025)
This research highlights the scientific efforts made by Dr. Akab Youssef Alawi Al-Rikabi in his book "Documentary Studies in the Contemporary History of Iraq," where he employed a number of family (personal) documents. These documents are unpublished and important for extracting historical events. By subjecting this book to research, analysis, and criticism of the texts of these documents and their uses in the book under study, we provided critical readings related to the events of these documents and the years they occurred, in accordance with the events mentioned in them and their historical references.